The determinants of bank profitability: evidence from Malaysia / Jaccielia Robinsin - Robinsin, Jaccielia (2015)
Profitability is the most important term that always been concerned by each companies and Banks in order to run a particular business. The conflict on the variables used in order to measures up and down of the bank profit has been existed and there are some studies that have different insight on the relationship between the variables used towards the bank profit. The purpose of this paper is to identify whether there is a significant relationship between liquidity, leverage and bank size towards bank profit or vice versa. Therefore, Current Asset (CR), total equity to total asset and Logarithm of Total asset was selected to indicate measurement of bank profit in order to analyze the relationship between the variables used towards bank profit. Panel data will be conduct for this research methodology and used data from 10 banks which consist of five Islamic Banks and another five Conventional Banks in Malaysia. In conclusion, this paper found that leverage and bank profit has significant positive relationship while liquidity and bank size have significant negative relationship towards bank profit.